A state of the art review on the novel mediator asprosin in the metabolic syndrome. Issue 6 (10th November 2020) - Luís, Carla; Fernandes, Rúben; Soares, Raquel; von Hafe, Pedro
Abstract : Abstract: Metabolic syndrome is a complex and heterogeneous pathology characterized by a cluster of biochemical, clinical, and metabolic factors that came together in raising the risk of cardiovascular diseases, type 2 diabetes mellitus, and all-cause mortality. Some of these features are well defined in this syndrome like: obesity, inflammation, hypertension, insulin resistance, atherosclerotic dyslipidemias, endothelial dysfunction, and inflammation. This circuit is intermediated by a complex network of hormones, cytokines, transcription factors, and adipokines, among others. Some like leptin, adiponectin, Plasminogen activator inhibitor-1, interleukin-6, Tumor necrosis factor, and their influence on the metabolic syndrome are well described in the literature and new players are described continuously. One novel player was described in 2016 by Romere et al as a fasting-induced glycogenic protein hormone named asprosin. In order to perform a state-of-the-art, nonsystematic review of asprosin, a study of the available literature was carried out in the main database (Pubmed) and the results were studied and correlated to better understand the mechanism of action of this hormone. Asprosin is not only associated with the metabolic syndrome features like glucose and lipid metabolism, insulin resistance, obesity and inflammation but also in other pathologies metabolic syndrome related like diabetic retinopathy, polycystic ovary syndrome and anorexia nervosa. A limited number of pathways were already unveiled although much more research is needed to better understand the therapeutical potential of asprosin in the metabolic syndrome.